Front Cover: Effective Photosensitization in Excited‐State Equilibrium: Brilliant Luminescence of TbIII Coordination Polymers Through Ancillary Ligand Modifications (ChemPlusChem 10/2022). Issue 10 (5th August 2022) - Kitagawa, Yuichi; Moriake, Ryoma; Akama, Tomoko; Saito, Koki; Aikawa, Kota; Shoji, Sunao; Fushimi, Koji; Kobayashi, Masato; Taketsugu, Tetsuya; Hasegawa, Yasuchika
Abstract : The cover picture shows a photosensitizer that has a long excited‐state lifetime and provides strong emissions for Tb III coordination polymers. The coordination polymers are composed of Tb III ions (emission center), hexafluoroacetylacetonato (photosensitizer ligands), and phosphine oxide‐based bridges (ancillary ligands). The photosensitizer with a long excited‐triplet‐state lifetime (τ≥1120 μs) controls the excited state equilibrium between the photosensitizer and Tb III, allowing the construction of Tb III coordination polymer with high Tb III emission quantum yield. More information can be found in the Research Article by Y. Kitagawa, Y. Hasegawa, and co‐workers .